The circumstances of literacy numeracy skill: Between notion and fact from elementary school students - Yeni Rakhmawati; Ali Mustadi (Jurnal Prima Edukasia, 2022)
Literacy activities in Indonesia are intensively developed to form literate citizens. Literacy is defined as a basic ability to develop individual potential in achieving goals. One of the literacies developed is numeracy literacy, which was coined in 2017. Numerical literacy is a branch of mathematical literacy. This ability guides individuals to recognize the role of numeracy competencies in everyday life. The knowledge of numeracy literacy is an urgent need for students. The student at least has received numeracy literacy development. This study aims to describe numeracy literacy in the field and compare numeracy literacy targets with reality in the area. The research method is descriptive quantitative. The data collection technique used a test with a research instrument of numeracy literacy skills and used non-test data, namely observation, and open interview guidelines. The research findings show that the students' numeracy literacy skills are still in the poor category. Numeracy literacy has not been developed in the implementation of the Gerakan Literasi Sekolah (GLS). Basic literacy activities have not been implemented properly.